Racism of the Main Character in 42 Movie Directed by Brian Helgeland - Yastanti, Unpris; Rohati, Titi Dewi; Akbar, Jamaluddin Muhamad (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
The purpose of this research is to identify the types of racism and the effect of racism on the main character in 42 movies directed by Brian Helgeland. The method of this analysis is the descriptive qualitative method. The results of this research are 1.) The types of racism of the main character are Individual Racism and Cultural Racism. 2.) There are three effects of racism on the main character; the social relation of the main character to his teammates, the violence of his opponent, and injury because of violence.